2012
DOI: 10.1186/2047-783x-17-29
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous core needle biopsy versus open biopsy in diagnostics of bone and soft tissue sarcoma: a retrospective study

Abstract: BackgroundBiopsy is a crucial step within the diagnostic cascade in patients with suspected bone or soft tissue sarcoma. Open biopsy is still considered the gold standard. However, recent literature suggests similar results for percutaneous biopsy techniques. Therefore, the aim of this retrospective analysis was to compare open and percutaneous core needle biopsy (CNB) regarding their accuracy in diagnosis of malignant musculoskeletal lesions.MethodsFrom January 2007 to December 2009, all patients with suspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
105
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 21 publications
(31 reference statements)
2
105
2
4
Order By: Relevance
“…2,3,9,11,12 A recent meta-analysis 14 of both bone and soft tissue tumors suggested that CB was more accurate than FNA, and incisional (open) biopsy appeared to be more accurate than both of those techniques; however, the differences did not reach statistical significance. Our results support the findings of the study by Pohlig et al, 15 which found percutaneous biopsy techniques (fine-needle aspiration and core needle biopsy) yielded slightly superior, but not statistically significant, results compared with OB. With the 31 lesions sampled by FNACBP as the initial diagnostic procedure in this study, 97% were diagnostic, compared with 79% and 78% for CB and OB, respectively.…”
Section: Resultssupporting
confidence: 83%
“…2,3,9,11,12 A recent meta-analysis 14 of both bone and soft tissue tumors suggested that CB was more accurate than FNA, and incisional (open) biopsy appeared to be more accurate than both of those techniques; however, the differences did not reach statistical significance. Our results support the findings of the study by Pohlig et al, 15 which found percutaneous biopsy techniques (fine-needle aspiration and core needle biopsy) yielded slightly superior, but not statistically significant, results compared with OB. With the 31 lesions sampled by FNACBP as the initial diagnostic procedure in this study, 97% were diagnostic, compared with 79% and 78% for CB and OB, respectively.…”
Section: Resultssupporting
confidence: 83%
“…It might be omitted only in the case of clinically and radiologically unambiguous benign lesions, such as chondroma, osteochondroma, osteoid osteoma, simple bone cyst, fibrous dysplasia, or nonossifying fibroma. The different procedures such as fine-needle aspiration, core needle, and incisional biopsy have the objective to gain a representative tissue sample with minimal trauma [14]. The shortest distance to the lesion is not necessarily the optimal route [4].…”
Section: Bone Biopsiesmentioning
confidence: 99%
“…This procedure has to be performed by an expert orthopaedic oncologist in line with the planned resection and according to sarcoma principles [14]. The samples are taken from the periphery of the tumor due to the frequent presence of central necrosis [14]. It is reasonable to assume that the risk of local contamination is higher in comparison to needle biopsy, and this is related to the width of the biopsy tract and adequacy of hemostasis.…”
Section: Bone Biopsiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is useful for deep-seated lesions like pelvis and spine and performed under CT guidance (11). Less morbidity and fewer complication rates have been reported for percutaneous biopsy ranging between 0% and 17%, most commonly hematoma, bleeding and infection (2,5,10). …”
Section: Core Needle Biopsy (Cnb)mentioning
confidence: 99%